Implementasi Digital Signage untuk Digital Marketing Produk UMKM pada Komunitas Sentra Kreasi Bandung - Robbi Hendriyanto; Wardani Muhamad; Heru Nugroho; Anak Agung Gde Agung; Rini Handayani; Gita Indah Hapsari; Kristina Sisilia; Agus Maolana Hidayat; Pramitha Aulia (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Digital signage (DS) can be used by business actors (MSMEs) to maximize marketing activities in addition to using other digital media such as social media, websites, videos, and SEO. DS is also part of a system that helps manage marketing as a medium that regulates product information owned by members of the MSME community. In the MSME Community of Kampung Digital Sentra Kreasi (Sentra Kreasi) Bandung, which houses various MSME, it was found that until now community members have not used digital signage as their marketing medium. Through the provision of DS services, it is hoped that community members can maximize their marketing. The method of carrying out activities is through socializing the use of digital signage and training on the use of marketing management systems for members and administrators of the Sentra Kreasi. Digital Signage Service Implementation Activities and marketing management applications at the Sentra Kreasi are carried out through Community Service Activities carried out by lecturers and students of the Faculty of Applied Sciences (FIT) and the Faculty of Communication and Business (FKB).